2009
DOI: 10.1111/j.1523-5378.2009.00707.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Helicobacter pylori Infection

Abstract: The articles published this last year in the field of Helicobacter pylori diagnosis reported the development of in vivo histology, small improvements in some invasive methods (urease test, culture, and histology) and new kits for the stool antigen tests. They also contributed to increasing our knowledge, by further exploration into specific conditions for the urea breath test and into the significance of cagA antibodies. The role of serum markers of atrophy was also confirmed. Molecular methods are still being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Real-time PCR is faster and offers several important advantages over conventional PCR; quantification and possibility for detection of mutations associated with antibiotic resistance. 1,20,28,29 Real-time PCR has therefore become the routine method for detecting H. pylori in our hospital.…”
Section: Articlementioning
confidence: 99%
“…Real-time PCR is faster and offers several important advantages over conventional PCR; quantification and possibility for detection of mutations associated with antibiotic resistance. 1,20,28,29 Real-time PCR has therefore become the routine method for detecting H. pylori in our hospital.…”
Section: Articlementioning
confidence: 99%
“…Also, it has been observed that the positivity for CagA antibodies has the ability to predict the development of atrophy and appears related with young gastric cancer cases (10). However, the accuracy of the tests developed with this regard has been questioned because the results differed when they were used in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…Among all, the serologic methods have been successfully used due to the immunogenicity of this protein and the non-invasivity of the method (10). In addition, it has been observed that CagA seropositivity is able to predict the development of atrophy and constitute a risk factor for intestinal metaplasia (11).…”
Section: Introductionmentioning
confidence: 99%
“…The reliability of serological kits for H. pylori infection has been widely confirmed [21], contributing to the reputation of serology as a simple, minimally invasive and inexpensive diagnostic and screening test. The best available serology test at the time of the study was the Pyloriset® an EIA-G from Orion Diagnostica, Espoo, Finland, with a specificity of 79–91% as assessed in previous studies in the Netherlands, including patients on acid suppressive therapy [22–24].…”
Section: Conclusion and Discussionmentioning
confidence: 99%